Synthesis and characterization of poly(vinyl alcohol-co-aspartic acid) copolymers - Tudorachi, N.; Lipsa, R. (Polimery, 2010)
The study presents synthesis of vinyl alcohol and L-aspartic acid copolymers (PVA-co-Asp), by solution polycondensation procedure using manganese acetate as a catalyst. Two copolymers were obtained with molar ratio of poly(vinyl alcohol) (PVA) structural unit to aspartic acid equal to 10/0.5 and 10/1, respectively. PVA and copolymers were investigated using Fourier transform infrared spectroscopy (FT-IR), but copolymers also with nuclear magnetic resonance ( H NMR). Molecular weight (Mω) and limiting viscosity numbers ([η|] of these polymers were also determined. With a system for simultaneous thermogravimetric and differential scanning calorimetry analyses (TG-DSC) thermal stability of PVA and its copolymers was investigated and compared. There was also defined zeta potential of water dispersions of PVA and copolymers and also dimensions and polydispersity of copolymer particles.